AI Education in Nigerian Schools - Niyi Jacob Ogunode; Olowonefa Jethro Abiodun (International Journal on Human-Computing Studies, 2023)
This paper examined the problems facing development of Artificial intelligence (AI) education in Nigerian Schools. Secondary data were used in the paper. The data were collected from print and online publications. The paper concluded that Artificial intelligence (AI) can be applied in preparation of students result report, school administration, aid effective learning, effective teaching implementation (intelligent tutoring), virtual learning environment and effective data management. The paper also identified funding problems, shortage of AI teachers, inadequate infrastructure facilities (laboratories), shortage of instructional materials and lack of sound AI curriculum as problems facing development of teaching and learning of AI in Nigerian schools. Based on tis problems identified, the paper hereby suggested the following: increment in funding of education; employment of Al professionals, provision of modern infrastructure facilities and development of sound Al curriculum for al level of education.